POSTOPERATIVE WOUND INFECTION IMPACT ON LONG TERM ONCOLOGICAL OUTCOMES IN RECTAL CANCER PATIENTS - V. V. Polovinkin; S. O. Ivanovsky; S. V. Khmelik; S. N. Scherba (Инновационная медицина Кубани)
Background. Now there are heteropolar opinions on influence of postoperative purulent septic complications on rectal cancer patients on the long term oncological results.Objective. Assess influence of these complications following laparotomy and perineal wounds after operations for rectal cancer on the long term oncological results.Methods. We performed retrospective cohort research of 338 patients undergone scheduled radical operations for middle ampullar and lower ampullar rectal cancer T1-4N0-2M0 from January, 2003 to December, 2011. Patients were distributed in two groups: with suppuration of postoperative wounds and/or abscess of the abdominal cavity (n = 44–13%) and without purulent septic complications (n = 294).Results. The logit regression analysis has shown that suppuration of laparotomy wounds and/or abscess of the abdominal cavity is one of the independent risk factors of a systemic recurrence. For development of a local recurrence purulent septic complications were not risk factors. The five-year overall and cancer specific survival in compared groups demonstrated statistically significant distinction. The overall survival in the main group – 47%, in the control one – 67.2% (Wilcoxon’s criterion р = 0.10, Cox-Mentela’s criterion р = 0.02, log rank criterion р = 0.03). Cancer specific survival was 43.5% and 70.1% respectively (Wilcoxon’s criterion p = 0.01, Cox-Mentela’s criterion p = 0.005, log rank criterion p = 0.009). The five-year recurrence free survival in the compared groups was similar 50.6 and 69% respectively (Wilcoxon’s criterion p = 0.25, Cox-Mentela’s criterion p= 0.12, log rank criterion p = 0.12).Conclusion. Purulent septic complications of postoperative wounds in patients with rectal cancer have impact on long term results: they are independent risk factor for systemic recurrence development and decrease total and cancer specific survival rate.